ANALISIS EFEKTIVITAS PROGRAM PENCEGAHAN DAN PENANGANAN KEKERASAN DI SEKOLAH DAN MADRASAH - Noer, Khaerul Umam; Putra, Sipin; Ghozi, Ahmad; Madewanti, Ni Loh Gusti; Widiyowati, Turisih (Gapenas Publisher, 2024)
Violence in schools is a serious problem that has a broad impact on the quality of education and the welfare of students and teachers. Violence does not only refer to physical acts but also includes psychological, verbal violence and cyberbullying. Preventing and handling violence in schools is crucial because of the significant negative impact on children's development and the school environment. This article focuses on preventing and handling violence in schools, supported by data on violence in schools, its impact on teachers and students, as well as Indonesian government policies in dealing with the problem of violence. This article is an inseparable part of the collaborative work between University of Muhammadiyah Jakarta and Perguruan Attaqwa, with full support from the Ministry of Education, Culture, Research and Technology. By using mixed research methods, and a program effectiveness theory approach, research shows that the program for preventing and handling violence in schools and madrasah carried out by Perguruan Attaqwa has proven to be effective in encouraging the presence of schools that are safe and free from violence. This condition arises because of the strict regulations and standard operational procedures used to handle and prevent violence, but also because the mentoring process is carried out continuously. On the other hand, schools that are safe from violence also exist because of a shared commitment from all parties, that violence in schools must be eradicated. This research shows that for a program to prevent and handle violence to be successful, it requires rules, understanding and commitment from all parties, so that it can achieve the expected results, namely schools that are safe and free from violence